Did statutory insurance improve the welfare of Swedish workers? The statutory workplace accident insurance act of 1916. (4th March 2022) - Andersson, Lars-Fredrik; Eriksson, Liselotte; Harris, Bernard
ABSTRACT: Welfare researchers have regarded statutory accident insurance in 1916 as a starting point for the exceptional expansion of the Swedish welfare state. However, rather less attention has been paid to the roles played by mutual insurance societies and employer compensation schemes in offering voluntary welfare protection. We argue that voluntary welfare protection was an integral part of the early-twentieth century welfare system and played a crucial role in protecting workers in the case of sickness and accident. We also examine the limitations of these arrangements and explore the ways in which the design of the statutory scheme ensured that there was a continuing role for voluntary provision after the new Act came into operation. We also explore the impact of the scheme on wage levels, and show how its introduction eroded the wage premiums which had previously been earned by workers in high-risk industries.